MiR-124a Regulates Extracellular Vesicle Release by Targeting GTPase Rabs in Lung Cancer - Romano, Giulia; Nigita, Giovanni; Calore, Federica; Saviana, Michela; Le, Patricia; Croce, Carlo M.; Acunzo, Mario; Nana-Sinkam, Patrick (Frontiers in Oncology, 2020)
Lung cancer is the leading cause of cancer mortality worldwide. Increased understanding of the molecular mechanisms of the disease has led to the development of novel therapies and improving outcomes. Recently, extracellular vesicles (EVs) have emerged as vehicles for the transfer of genetic information between tumors and their microenvironment and have been implicated in lung cancer initiation, progression, and response to therapy. However, the mechanisms that drive the biogenesis and selective packaging of EVs remain poorly understood. Rab family guanosine triphosphates (GTPases) and their regulators are important membrane trafficking organizers. In this study, we investigated the role of select Rab GTPases on the regulation of EV release. We found that microRNAs target Rab GTPases to regulate EV release from lung cancer cell lines. In particular, Rab32 is a target of miR-124a, and siRNA and miRNA mediated inhibition of Rab32 leads to impaired EV secretion. The downstream implications for microRNA-based regulation of EV release are currently under investigation.